PENERAPAN METODE FUZZY SUGENO SEBAGAI SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN CALON PRESIDEN MAHASISWA - Erica Prasetyaning Putri (Universitas Negeri Surabaya, 2020)
The student president is the leader of the students, who functions as a mediation between students and the rector, especially in conducting interaction relationships for the continuation of the communicative academic process. The student president himself will be chosen directly by the campus community from among several student presidential candidates. In determining student presidential candidates, there is a stage where the committee must examine and compare the quality of one nominee to another to select students who volunteered to become candidates who will have the opportunity to be elected later. Therefore, a decision support system was designed to determine student presidential candidates using the Sugeno fuzzy method. Sugeno fuzzy method is able to facilitate the student presidential election committee in determining student presidential candidates in accordance with specified conditions. Keywords: Student president, decision support system, and sugeno fuzzy.